Spatiotemporal dynamics and driving factors of eco-environmental quality in the sandy areas of Western Inner Mongolia (2000–2024) - Yang, Shuchang; Meng, Zhongju; Meng, Ruibing (Frontiers in Environmental Science, 2025)
The Inner Mongolia Western Sandy Area (IMWSA) is a vital component of China’s northern ecological security barrier, with its ecological environment highly sensitive to both climate change and human activities. Investigating the spatiotemporal dynamics of the eco-environmental quality (EEQ) in this region is essential for enhancing ecological governance and promoting sustainable development in sandy areas. Building on the traditional Remote Sensing Ecological Index (RSEI), this study adapted it to the ecological characteristics of the IMWSA by incorporating five indicators—greenness, humidity, land surface temperature, dryness, and salinity—to develop an enhanced eRSEI model suitable for regional EEQ assessment. Using this model, the spatiotemporal evolution of EEQ in the IMWSA from 2000 to 2024 was systematically analyzed. The optimal-parameter Geodetector Model (GDM) and partial correlation analysis were employed to identify the driving factors responsible for its spatial differentiation and temporal variation. We found that EEQ was generally better in the southeast and declined towards the northwest. During the study period, the eRSEI exhibited an overall upward trend, at a rate of 0.0056 per decade, indicating a general improvement in EEQ, with the spatial extent of significant improvement (9.52%) clearly exceeding that of significant deterioration (1.69%). The Hurst exponent of the IMWSA was 0.38, which indicated anti-persistent characteristics and suggested that future EEQ improvement might slightly outweigh deterioration. Land use types and meteorological variables were the main driving factors influencing the spatial distribution and variation of eRSEI. Positive correlations were observed between eRSEI and temperature, precipitation, and solar radiation, with precipitation showing the strongest association. Recent climate change has generally hindered EEQ improvement. In contrast, human-induced land use changes, particularly ecological restoration, have enhanced vegetation cover and regional microclimates, resulting in an average eRSEI increase of 0.07 in areas where land use had changed compared to those that remained unchanged, making them the primary drivers of ecological improvement.